ANALYSIS OF THE PRODUCTION CHAIN OF A FISHING COMMUNITY IN BAHIA SOUTH TARGETING ITS ECONOMIC DEVELOPMENT - Behrmann, Daianne Gabrielle Morais; Universidade Estadual de Santa Cruz - UESC (2017)
This article aims to characterize the links in the production and marketing of the production chain of fisheries, from the perspective of fishermen. Primary and secondary source data were used. Primary data was collected through observation techniques, field diary and semi-structured interviews with fishermen, while the secondary data through bibliographical and documentary research. The survey revealed the precarious infrastructure for production, especially with regard to fish packaging, making it impossible to maintain inventory, and thus limiting commercial activity. Denotes the relationship of interdependence between economic agents and the need for cooperation. The difficulties imposed by the production infrastructure and existing storage, dependence on few buyers and limited systemic view by fishermen, fall as major bottlenecks in the production chain of fisheries in the analyzed community.